Preference of consumer towards imported rice and local rice in Kelantan - Zul Ariff Abdul Latiff; Mohammad Amizi Ayob (2017)
Aim/Purpose This research seeks to determine the consumer preferences between local and import rice by using theory of knowledge, attitude and perception model (KAP). Background Rice industry has received special attention from the government and was put as the most important food crop for ensuring the nation’s food security. This study tries to reveal the preferences of the consumer for imported rice as compared to local rice based on their knowledge, attitude and perception. Methodology The simple random sampling technique is adopted in selecting 154 rice consumers in the Kelantan area. 154 questionnaires were distributed to them. Contribution This paper studies the preferences of the consumer for local and imported rice. The findings presented and conclusions reached could be of interests to consumers, researchers, society, manufacturers and government. Findings The findings from factor analysis supported the proposed model indicated that consumer knowledge is the first factor that influenced consumer preference on the rice followed by perception and attitude. It is also suggested that the demographic factor have a relationship with consumer preference based on their knowledge, attitude and perception. Recommendations for Practitioners The consumer knowledge of local rice in Malaysia should be promoted more through television and social media as this influences their attitude when purchasing rice at the market. The quantity and the availability of the local product should be based on the majority of the consumers that usually shop for rice in